Related Fixed Point Theorems via General Approach of Simulations Functions - Kastriot Zoto; Nabil Mlaiki; Hassen Aydi (Journal of Mathematics)
In this work, we extend and complement some results in view of general and wider structures, such as b−metric spaces. By considering existing classes of Ζ−contractions and Ψ−simulating functions with a solid impact in database results of fixed point theory, we introduce a new general class of simulating functions, called as Ψ−s simulation functions, and also types of κψ−s− contractions in a more general framework. This approach covers, extends, and unifies several published works in the early and late literature.